Pigeonpea sterility mosaic emaraviruses: a journey from a mysterious virus to classic emaraviruses - Patil, B.L.; Kumar, P. Lava (Springer, 2017)
Sterility mosaic disease (SMD) of pigeonpea (Cajanus cajan (L.) Millsp) first reported in 1931, is an economically most important viral disease, which is endemic to India, Nepal, Bangladesh and Myanmar. SMD was long suspected to be a viral disease, however its causal agent, pigeonpea sterility mosaic virus (PPSMV) was discovered only in 2000. In 2013, the full genome of PPSMV was sequenced and based on the genome organization the virus was assigned to the genus Emaravirus. In 2015, association of another distinct emaravirus in SMD affected pigeonpea was discovered and it was named as pigeonpea sterility mosaic virus 2. As per the latest ICTV classification, these two pigeonpea infecting emaraviruses are renamed and recognised as two different virus species, Pigeonpea sterility mosaic emaravirus 1 and Pigeonpea sterility mosaic emaravirus 2 under the family Fimoviridae of the order Bunyavirales. These two emaraviruses involved in SMD are transmitted in a semi-persistent manner by an eriophyid mite, Aceria cajani Channabassavanna (Acari: Arthropoda). These viruses and its eriophyid vector are highly specific to pigeonpea and its wild relatives. This chapter presents the review of the studies conducted on SMD of pigeonpea and PPSMVs in India.